2019
DOI: 10.1080/11356405.2019.1601937
|View full text |Cite
|
Sign up to set email alerts
|

The credibility of online news: an evaluation of the information by university students / La credibilidad de las noticias en Internet: una evaluación de la información por estudiantes universitarios

Abstract: The spread of online disinformation is one of the 10 global risks of the future according to the World Economic Forum, and 51% of experts believe that this situation will not improve in the coming years. By 2022, half of the news will be fake news. In terms of users, young people and adults have problems understanding where the information they find online comes from and what sources to trust or not. In order to ascertain the degree of credibility that young users in Andalucía give to information, this study p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 28 publications
2
17
0
7
Order By: Relevance
“…Thus, young Spanish adults believe they know how to identify fake news but do not use the optimal tools for its verification. These results are corroborated by those provided by the "Study on the impact of fake news in Spain" [39] which revealed that more than fifty percent of young people believed they knew how to identify fake news but that only 4% actually knew how to, and by those of Herrero, Conde, Tapia and Varona [7], who concluded that young adults have difficulties in differentiating the veracity of sources.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Thus, young Spanish adults believe they know how to identify fake news but do not use the optimal tools for its verification. These results are corroborated by those provided by the "Study on the impact of fake news in Spain" [39] which revealed that more than fifty percent of young people believed they knew how to identify fake news but that only 4% actually knew how to, and by those of Herrero, Conde, Tapia and Varona [7], who concluded that young adults have difficulties in differentiating the veracity of sources.…”
Section: Discussionsupporting
confidence: 69%
“…In Spain -the subject of our study-, the level of credibility that young university students studying a degree in Communication and Education at the Loyola Andalusia University give information has been investigated, revealing differences both in terms of gender and level of studies [7]. This field of study was expanded by Mendiguren, Dasilva, and Meso [18], who studied whether university students who study journalism at the University of the Basque Country knew how to identify fake news, if they believed they had the criteria to distinguish it, and how they verify information when they suspect that it lacks rigor, as well as the credibility they give mainstream media and the dissemination of news they trusted least.…”
Section: Young Adults and Fake Informationmentioning
confidence: 99%
“…Bien por omisión de contenidos, bien por modificación intencionada de la verdad, los ciudadanos están inmersos en un information disorder (Wardle y Derekhshan, 2017) que hace cuestionar cada vez más el derecho a recibir información veraz, sobre todo cuando el 51% de los expertos considera que en 2022 el 50% de las noticias serán falsas (Herrero-Diz, Conde-Jiménez, et al, 2019). Es precisamente la intencionalidad lo que distingue una fake new de una información falsa o inexacta (Egelhofer y Lecheler, 2018), pero lo cierto es que a los públicos cada vez les resulta más complicado distinguir entre la información sin sentido (nonsense information) creada por algoritmos y la que es fabricada con una intencionalidad económica (Bridle, 2018), aunque, en realidad, la falta de alfabetización digital y mediática imposibilitan a muchos ciudadanos determinar qué sitios web son fiables y cuáles no.…”
Section: Nuevas Oportunidades Para Informarse Y Nuevas Amenazas Para Desinformarseunclassified
“…Sin embargo, sí serían extrapolables el propio estudio y el cuestionario diseñado, ya que pueden ser empleados por el profesorado como un paso previo y preparatorio antes de trabajar en sus clases la temática de las fake news. Pues cada vez son más frecuentes las experiencias y los proyectos docentes relacionados con la identificación y el tratamiento de este tipo de contenidos digitales (Auberry, 2018;Cebrián Robles, 2019;Herrero-Diz et al, 2019;Musgrove et al, 2018).…”
Section: Metodologíaunclassified